PENERAPAN METODE MODELING THE WAY DALAM PEMBELAJARAN MEMBACA PUISI PADA SISWA KELAS X SMK PLUS AS-SALAFIYAH KRANGKENG TAHUN AJARAN 2024/2025 - Khusna, Asmaul; Hasanudin, Ade; Muthmainnah, Fithry (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The direct learning method focused on information delivery used by teachers is considered less enjoyable by students, forming the basis of this research. The enthusiasm for learning has decreased as a result. This study aims to examine how the model learning method is used to teach poetry to students in the X grade at SMK Plus As-Salafiyah Krangkeng in the 2024/2025 academic year and, secondly, to determine how students participate in using this approach to teach poetry to X grade students at SMK Plus As-Salafiyah Krangkeng in the 2024/2025 academic year. All X grade students at SMK Plus As-Salafiyah Krangkeng in the 2024/2025 academic year are the population of this research, which is conducted using experimental methods. With the saturated sampling technique, 20 students from class X TKJ were designated as the experimental class, and 20 students from class X TO were designated as the control class. We collected research data through observation sheets and written tests. The results of the statistical calculations using the independent two-sample t-test show that t-observed is 3.456 and t-table is 2.024, respectively. The result pertains to the t-test sample that did not receive acceptance. Therefore, t-observed 3.456 is greater than t-table 2.024, indicating that Ha is accepted and Ho is rejected. The tenth-grade students at SMK Plus As-Salafiyah Krangkeng have thus found success with the poetry learning approach for the 2024–2025 school year. modeling the way. As shown by the analysis of the observational data, this method has the potential to increase student engagement in the poetry learning process.